Legal Protection And Certainty Over The Implementation Of Emergency Interim Relief In The Arbitration Dispute Resolution Process In Indonesia - Sulistiono, Sandy; Octarina, Nynda Fatmawati (Journal of Law, Politic and Humanities, 2025)
This study explores the urgency and legal framework of Emergency Interim Relief (EIR) in Indonesian arbitration law, emphasizing its role in safeguarding parties’ rights and ensuring legal certainty in urgent disputes. EIR, as a temporary measure issued before a full arbitral tribunal is constituted, is crucial for preventing irreparable harm such as asset dissipation or evidence destruction. Although Law No. 30 of 1999 grants tribunals the authority to issue interim measures, its lack of explicit enforcement mechanisms historically limited their effectiveness. The issuance of Supreme Court Regulation No. 3 of 2023 (PERMA 3/2023) marks a significant development by providing procedural clarity, mandating court registration of interim orders, and introducing fixed timelines for enforcement, including for foreign awards. These reforms align Indonesian arbitration practice more closely with international standards and enhance its attractiveness as a dispute resolution hub. However, limitations remain, notably the narrow scope of PERMA 3/2023, which primarily addresses security seizures, and uncertainties regarding the enforceability of emergency awards under institutional rules such as the 2025 BANI Rules.